5a+3(a+3)-a=a

Simple and best practice solution for 5a+3(a+3)-a=a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+3(a+3)-a=a equation:



5a+3(a+3)-a=a
We move all terms to the left:
5a+3(a+3)-a-(a)=0
We add all the numbers together, and all the variables
3a+3(a+3)=0
We multiply parentheses
3a+3a+9=0
We add all the numbers together, and all the variables
6a+9=0
We move all terms containing a to the left, all other terms to the right
6a=-9
a=-9/6
a=-1+1/2

See similar equations:

| k/4=25 | | (4x)=24 | | 95=-8x=14 | | 5m=–45 | | 1.2x^2-0.7x-22.4=0 | | 3^(x-3)=15 | | (5x)=120 | | 7x4=11 | | J5+2j=7 | | -9=4p+3 | | 150=1/2(b1+9)12 | | 2x+6=16-10x | | 5(1)+5x=12 | | 9=2k-1 | | -3r=3.42 | | x+7/​2x=9 | | 2.5x–5=5 | | 10+1/3(x+7)=2 | | -1.5x+0.429=0.5 | | x+​7/​2x=9 | | (4+g)(−11)=121 | | 4(2x-4)+3=11 | | 19t=-323 | | 3m+5=20-2m | | 99=11r | | x−7=32−11(x+9) | | 5=11y+ | | 63=70-7(x) | | 5x-3-2x=2x-1 | | 12j=240 | | 5w=-4=9w | | f+2+3=50 |

Equations solver categories